Investigating the psychological impact of COVID‑19 on frontline medical staff and coping strategies during the disease outbreak in the medical centers of Rasht, IRAN, 2020 - Maryam Khoshbakht-Pishkhani; Maryam Zaer Sabet; Elnaz Faraji Nesfechi; Saman Maroufizadeh; Maryam Hosseinzadeh; Jannat Soleimani Kamran; Shahrbanoo Akhlaghnejat (Elsevier, 2023)
Background: Coping strategies to minimize the psychological impact of diseases and epidemics on the medical staff is essential. This study aims to investigate the psychological impacts of COVID-19 and the coping strategies of frontline medical staff in the fight against this disease. Methods: This analytical cross-sectional study was conducted in 2020 in Rasht, Iran 0.248 Medical Staff participated through convenience sampling and an online questionnaire. The questionnaires included two sections: Demographic characteristics and Coping strategies and the emotional impacts consisting of five dimensions and 67 questions (Scores 0-3). The two-sample t-test was used to compare the responses between gender, age, and Medical staff groups. Data were analyzed using SPSS software version 16. Results: The most critical item for the staff in the 'emotion' dimension was expecting a decrease in their relationship with the individuals who were not exposed to the disease (p < 0.026). The most important stressor was infection by an infected patient under their care (p < 0.009) in non-nursing medical staff. Concerning stress-reducing factors, the most important factor was hospital support soon after becoming infected (p < 0.039). The most important stress-reducing coping strategy was adherence to personal protective equipment use by the nursing staff. Conclusion: Due to the high prevalence of mental disorders in staff involved in the care for patients with COVID-19, paying attention to staff emotions and stress-reducing factors and increasing access to protective equipment and proper crisis management against the disease can greatly reduce the psychological disorders and more prepared them for epidemics crisis.